Perfil do adoecimento dos trabalhadores de câmpus universitário do interior paulista: análise dos dados de absenteísmo por motivo de doença - Fantazia, Miriam Malacize [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The profiles of illness and death among workers have changed with the introduction of new production and work methods in society, both in private and in public institutions. In public institutions, recent changes, starting in the 90s, include new management and work organization methods that entail better productivity, faster paced work, employee downsizing, temporary staffing and outsourcing, and labor market flexibility among others. As a result, the rates of physical and mental illness among public servants have increased leading to illness-related absence, defined as time off from work due to illness certified by a physician/sick leave. The objective of this study was to establish the profile of illness-related absence among statutory workers of a Brazilian state public university, in 2012. In this cross-sectional study, secondary data extracted from the institution's occupational medical examination systems and medical reports were analyzed using IBM SPSS Statistics software (v.21.0). The results have been reported as simple and cumulative frequencies, associations estimated by chi-square tests, and distribution differences determined by post-hoc Z tests with Bonferroni's correction coefficient. During the study period, 538 workers were on sick leave. Workers consisted of married females aged over 41 years. Most of them had been working on the institution's hospital of clinics for 11-30 years holding intermediate level nursing positions, and had taken leave once. Of these, 11% were provided with job accommodation. The most frequent causes for leaves, which lasted for up to 15 days, were mental/behavioral disorders, and osteomuscular and connective tissue diseases. Statistical analysis demonstrated that some sociodemographic characteristics, such as sex and age, and job characteristics, such as work unit and position, influenced the development of illness, which in turn influenced leave duration and job accommodation ...

O perfil de adoecimento e mortalidade de trabalhadores vem mudando na medida em que são alterados os modos de produção e de trabalho na sociedade, atingindo instituições privadas e públicas. Nas instituições públicas, as recentes mudanças ocorrem a partir da década de 90 e preveem a adoção de novos mecanismos de gestão e de organização do trabalho, com exigência de maior produtividade, aumento de ritmo, enxugamento do contingente de trabalhadores, contratações com vínculos precarizados e terceirizados, flexibilização dos direitos e da remuneração dos trabalhadores, entre outros. Resultante desta dinâmica, surgem índices elevados de adoecimento físico e mental entre os trabalhadores públicos, ocasionando o absenteísmo-doença, considerado como a ausência ao trabalho relacionada à doença e justificada por atestado/licença médica. A presente pesquisa teve o objetivo de estabelecer o perfil de afastamento por motivo de doença de trabalhadores estatutários de câmpus universitário do interior paulista no ano de 2012. O estudo foi transversal com utilização de dados secundários extraídos de sistemas de atendimentos ocupacional e pericial da instituição, analisados no programa estatístico IBM SPSS Statistics (v.21.0), e os resultados apresentados em frequências simples e acumuladas, em associações estimadas por testes do quiquadrado e por aplicação de testes post-hoc Z com coeficientes de correção de Bonferroni para determinação das diferenças entre as distribuições. Os dados mostram que em 2012, 538 trabalhadores do regime estatutário se afastaram do trabalho por motivo de doença. O perfil destes trabalhadores é composto por pessoas do sexo feminino, casado, com idade superior a 41 anos, sua maioria lotada no hospital das clínicas universitário, com cargos de nível médio da área da enfermagem, e com 11 a 30 anos de tempo de serviço na instituição. A maioria teve um episódio de...
The profile of illness among workers of a university campus in the state of São Paulo: analysis of illness-related absenteeism
Keywords: Saúde do trabalhador; Absenteísmo (Trabalho); Setor publico; Saúde pública; Public health